Inversion of the Sign of the Short-Range Order as a Function of the Composition of Fe–Cr Alloys at Warm Severe Plastic Deformation and Electron Irradiation - Kirill Kozlov; Valery Shabashov; Andrey Zamatovskii; Evgenii Novikov; Yurii Ustyugov (Metals, 2020)
This paper presents the results of a Mössbauer spectroscopy investigation of the processes in the binary alloys Fe100−cCrc (c, at. % = 6.0, 9.4, 13.2) and of the short-range (SR) atomic ordering accelerated by applying warm severe plastic deformation via high pressure torsion (HPT). After warm HPT treatment, in the vicinity of the concentration c = 9 at. %, there was revealed to be an inversion of the sign of the SR order, the anomaly of the formation of a Fe–Cr solid solution, which was predicted ab initio and is observed at long-term anneals and exposures to irradiation by electrons. The acceleration of the SR ordering at HPT is due to the continuous generation and a large number density of mobile point defects.